Jawabanmu

2014-04-13T15:28:28+07:00
( 2  \sqrt{3} -  \sqrt{5}  )^{2}
= ( 2  \sqrt{3} -  \sqrt{5} ) ( 2  \sqrt{3} -  \sqrt{5} )
= 4 × 3 - 2 \sqrt{15} - 2  \sqrt{15} + 5
= 12 +5
= 17
( 2 \sqrt{3} - \sqrt{5} )^{2}
= ( 2 \sqrt{3} - \sqrt{5} ) ( 2 \sqrt{3} - \sqrt{5} )
= 4 × 3 - 2 \sqrt{15} - 2 \sqrt{15} + 5
= 12 +5=17
2014-04-13T15:31:49+07:00
Ada rumus begini =
(a-b)^{2}  =  a^{2} - 2ab +  b^{2}

nah, kita pake rumus itu
Jadinya,
((2 \sqrt{3} - \sqrt{5}) ^{2} =   (2\sqrt{3})^{2} - 2(2 \sqrt{3} .  \sqrt{5})^{2} +  (\sqrt{5})^{2} = a^{2} - 2ab + b^{2}

4.3 - 2(2 \sqrt{15} ) + 5
12 - 4 \sqrt{15} + 5
17 - 4 \sqrt{15}